tanq-cotq=2sin2q-1/sinqcosq
Attachments:
![](https://hi-static.z-dn.net/files/d9c/f639ee1fc7c62c4ed311d567828c2aa6.jpg)
Answers
Answered by
4
= tanq - cotq
= (sinq/cosq) - (cosq/sinq)
= (sin2q - cos2q)/(sinq*cosq)
= -(cos2q-sin2q)/(sinq*cosq) [here, minus is taken common]
= -(1-2sin2q)/(sinq*cosq) [since, cos2q-sin2q = 2cos2q-1 = 1-2sin2q ]
= now multiply minus inside
= (2sin2q-1)/(sinq*cosq)
= (sinq/cosq) - (cosq/sinq)
= (sin2q - cos2q)/(sinq*cosq)
= -(cos2q-sin2q)/(sinq*cosq) [here, minus is taken common]
= -(1-2sin2q)/(sinq*cosq) [since, cos2q-sin2q = 2cos2q-1 = 1-2sin2q ]
= now multiply minus inside
= (2sin2q-1)/(sinq*cosq)
Similar questions
Social Sciences,
8 months ago
Science,
8 months ago
Math,
1 year ago
Hindi,
1 year ago
Computer Science,
1 year ago